THE INFLUENCE OF PROJECT BASED LEARNING (PJBL) ON MATHEMATICAL COMMUNICATION SKILLS IN RELATION TO COGNITIVE STYLES - Nadia Amanda Sari; Irma Fitri (Universitas Muhammadiyah Lampung, 2025)
To know the effect of PjBL (Project Based Learning) learning model with Discovery Learning learning model on mathematical communication skills in terms of cognitive style is the purpose of this study. The type of research is quantitative research with factorial experimental design. The population of the researcher's study was class VII F, VII G, VII H, and VII I SMP Negeri 1 Pangkalan Kerinci. Data collection used mathematical communication ability test instrument, cognitive style GEFT test, and documentation. Data analysis techniques used normality test, homogeneity test, and two-way ANOVA. The results of this study are (1) There is a difference in the ability of students who learn using the Project Based Learning model to obtain better mathematical communication skills than Discovery Learning students. (2) There is a difference between students with a field independent cognitive style obtaining better mathematical communication skills than students with a field dependent cognitive style. (3) There is no interaction effect between Project Based Learning and cognitive style on mathematical communication skills. Keywords: (PjBL) Project Based Learning, Mathematical Communication, Cognitive Style